2020
DOI: 10.48550/arxiv.2006.03698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Texture Interpolation for Probing Visual Perception

Jonathan Vacher,
Aida Davila,
Adam Kohn
et al.

Abstract: Texture synthesis models are important to understand visual processing. In particular, statistical approaches based on neurally relevant features have been instrumental to understanding aspects of visual perception and of neural coding. New deep learning-based approaches further improve the quality of synthetic textures. Yet, it is still unclear why deep texture synthesis performs so well, and applications of this new framework to probe visual perception are scarce. Here, we show that distributions of deep con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Similarly, some have suggested that natural images can be represented as mixtures of textures which lie on a low-dimensional manifold (Vacher & Coen-Cagli, 2019;Vacher et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, some have suggested that natural images can be represented as mixtures of textures which lie on a low-dimensional manifold (Vacher & Coen-Cagli, 2019;Vacher et al, 2020).…”
Section: Related Workmentioning
confidence: 99%